Association between major depressive episode and risk of type 2 diabetes: a large prospective cohort study in Chinese adults - Meng, R; Liu, N; Yu, C; Pan, X; Lv, J; Guo, Y; Bian, Z; Yang, L; Chen, Y; Chen, Z; Pan, A; Li, L; et al. (Elsevier, 2018)
Objective We aimed to prospectively evaluate the association between major depressive episode (MDE) and risk of type 2 diabetes in a Chinese population. Methods We used data from the China Kadoorie Biobank study, in which 461,213 participants free of diabetes, coronary heart disease, stroke, and cancer were followed from baseline (2004-2008) to December 31, 2013. A modified Chinese version of Composite International Diagnostic Interview Short-Form (CIDI-SF) was used to assess past year MDE. Participants who responded positive to depression screening questions but did not meet the diagnosis criteria were considered as having depressive symptoms only. Incident diabetes cases were identified through linkage with established regional disease registries and national health insurance databases. Cox proportional hazards regression model was used to calculate hazard ratio (HR) and 95% confidence interval (CI) for the association after adjusting for diabetes risk factors. Results We documented 8784 incident type 2 diabetes cases during a follow-up of 3,291,908 person-years. We observed a higher incidence rate of type 2 diabetes in participants with MDE than those without, and the multivariable-adjusted HR was 1.31 (95% CI 1.04-1.66). Compared with participants without depressive symptoms, the HR (95% CI) was 1.19 (1.05-1.35) for participants with depressive symptoms only and 1.32 (1.05-1.68) for those with MDE. Limitations The prevelance of past year MDE based on CIDI-SF was low, which might result in a selection bias. Conclusions In our large prospective cohort study of Chinese adults, MDE was significantly and independently associated with an increased risk of type 2 diabetes.